2018
DOI: 10.1111/bjh.15741
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin, vinblastine, dacarbazine and lenalidomide for older Hodgkin lymphoma patients: final results of a German Hodgkin Study Group (GHSG) phase‐I trial

Abstract: Summary About 30% of all Hodgkin lymphoma (HL) patients are ≥60 years old. As lenalidomide has promising single agent activity in multiple relapsed HL, we replaced bleomycin in ABVD with lenalidomide in this phase‐I trial. Patients aged ≥60 years with early‐unfavourable‐ or advanced‐stage HL (Eastern Cooperative Oncology Group performance status ≤2, Cumulative Illness Rating Scale for Geriatrics score 0–7) received 4–8 cycles of AVD (doxorubicin, vinblastine, dacarbazine) and lenalidomide in escalation with ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In a recent trial, BV was associated with cyclophosphamide, doxorubicin and prednisone (B‐CAP); 1‐year PFS was 73.9%, grade 4 leukopenia and grade 3 peripheral neuropathy were observed in 41% and 20% of cases, respectively . Lenalidomide was investigated in combination with AVD in 25 elderly HL patients with CIRS 0‐7; 3‐year estimated PFS was 69.7% without treatment‐related deaths …”
Section: Patient's Characteristicsmentioning
confidence: 99%
“…In a recent trial, BV was associated with cyclophosphamide, doxorubicin and prednisone (B‐CAP); 1‐year PFS was 73.9%, grade 4 leukopenia and grade 3 peripheral neuropathy were observed in 41% and 20% of cases, respectively . Lenalidomide was investigated in combination with AVD in 25 elderly HL patients with CIRS 0‐7; 3‐year estimated PFS was 69.7% without treatment‐related deaths …”
Section: Patient's Characteristicsmentioning
confidence: 99%
“…Among these drugs, brentuximab has been explored either in combination with AVD in fit patients or with dacarbazine alone in patients with severe comorbidity, showing promising activity . Other drugs that are explored in this setting include lenalidomide and nivolumab …”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Other drugs that are explored in this setting include lenalidomide and nivolumab. 29,30 We also analyzed cause-specific survival. Our finding that the type of chemotherapy and the prognostic score were associated with lymphoma-specific survival and that the presence of severe comorbidity was associated with mortality form all other causes other than lymphoma was not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…As 14% of deaths were related to lung toxicity, the authors recommend bleomycin dose reduction or removal [9]. A phase I trial attempted to replace bleomycin with lenalidomide for Hodgkin lymphoma patients aged 60 years or above, and concluded that this approach was feasible and highly effective [10].…”
Section: Discussionmentioning
confidence: 99%